Antibiotic-Induced Changes in the Intestinal Microbiota and Disease. Issue 6 (June 2016) - Becattini, Simone; Taur, Ying; Pamer, Eric G.
Abstract : The gut microbiota is a key player in many physiological and pathological processes occurring in humans. Recent investigations suggest that the efficacy of some clinical approaches depends on the action of commensal bacteria. Antibiotics are invaluable weapons to fight infectious diseases. However, by altering the composition and functions of the microbiota, they can also produce long-lasting deleterious effects for the host. The emergence of multidrug-resistant pathogens raises concerns about the common, and at times inappropriate, use of antimicrobial agents. Here we review the most recently discovered connections between host pathophysiology, microbiota, and antibiotics highlighting technological platforms, mechanistic insights, and clinical strategies to enhance resistance to diseases by preserving the beneficial functions of the microbiota. Trends: The gut microbiota contains trillions of bacteria belonging to hundreds, possibly thousands, of species and is crucial for optimal maintenance of host physiological processes. The microbiota protects against infections and other pathologies by directly inhibiting invading microbes or by orchestrating appropriate immune responses; conversely, metabolites produced by some gut commensals can promote a variety of diseases such as atherosclerosis or cancer. Antibiotics alter the microbiota composition, resulting in an increased risk of disease, secondary infections, allergy, and obesity. In addition, they promote the spread of drug-resistant pathogens, making the search for alternative clinical approaches imperative. Novel strategies are being developed to substitute or complement antibiotic therapies, attempting either to selectively target pathogens without perturbing the microbiota and/or to re-establish commensal communities together with the protective and beneficial effects they confer to the host.